Модель гідравлічного приводу мехатронної системи з планетарним гідромотором - Панченко, Анатолій Іванович; Panchenko, Anatolii; Волошина, Анжела Анатоліївна; Voloshyna, Anzhela; Рожнятовський, В. В.; Засядько, Андрій Іванович (Одеса : Видавничий дім “Гельветика”, 2024)
UA: У статті розглянуто проблему підвищення ефективності та надійності гідроприводів самохідної техніки шляхом удосконалення методів аналізу динамічних процесів у гідроагрегатах з планетарними гідромоторами. Показано, що робота таких гідроприводів у змінних режимах супроводжується нестаціонарними гідравлічними та механічними процесами, які суттєво впливають на вихідні характеристики, енергетичні втрати та ресурс елементів системи. Встановлено, що існуючі методи розрахунку переважно базуються на спрощених стаціонарних моделях і не дозволяють у повній мірі врахувати взаємодію системи роторів та розподільної системи планетарних гідромоторів, а також вплив змінних навантажень. У роботі обґрунтовано доцільність застосування комплексних математичних моделей, які поєднують опис гідравлічних і механічних процесів та дають змогу досліджувати зміну тиску і крутного моменту в перехідних режимах роботи. Запропоновано підхід до дослідження динамічних характеристик гідроагрегатів з планетарними гідромоторами, який дозволяє оцінювати зміну тиску, витрати робочої рідини та крутного моменту в перехідних режимах роботи. Особливу увагу приділено аналізу впливу конструктивних параметрів планетарного гідромотора, зокрема геометрії робочих камер і характеристик розподільного блока, на нерівномірність крутного моменту та пульсації тиску. Отримані результати можуть бути використані при проєктуванні та модернізації гідроприводів мобільної техніки з планетарними гідромоторами. /// EN: This article examines the pressing scientific and technical challenge of increasing the efficiency of mechatronic hydraulic drives in self-propelled vehicles by improving methods for analyzing and modeling dynamic processes in hydraulic drives with planetary hydraulic motors. Modern self-propelled vehicles operate under variable loads and frequent starts and stops, leading to the emergence of non-stationary hydraulic and mechanical processes that significantly impact the output characteristics of hydraulic drives and their components. This paper analyzes current scientific research, revealing that existing hydraulic drive calculation methods are primarily based on simplified steady-state models and do not fully account for the dynamic interaction of the rotor system and the distribution system of planetary hydraulic motors, the compressibility of the working fluid, and the impact of non-stationary loads. Therefore, the need for an integrated modeling approach that combines the description of hydraulic and mechanical processes in a single mathematical model is justified. An approach to studying the dynamic characteristics of mechatronic hydraulic drives with planetary hydraulic motors is proposed. This approach allows for assessing changes in pressure, flow rate, torque, and rotational speed during transient operating conditions. Particular attention is paid to analyzing the influence of planetary hydraulic motor design parameters, in particular, the presence of a diametrical gap between the rotors and changes in the cross-sectional area of the distribution system, on the output characteristics of hydraulic drives and their components. The obtained results indicate that accounting for dynamic processes in mathematical models allows for improved accuracy in predicting the performance characteristics of mechatronic hydraulic drives with planetary hydraulic motors and creates the prerequisites for informed selection of design parameters during their design and modernization. The practical value of this work lies in the potential use of the proposed approaches in the development of energy-efficient hydraulic drives with planetary hydraulic motors and in further research aimed at optimizing their dynamic and energy performance.
Model of a hydraulic drive for a mechatronic system with a planetary hydraulic motor
Keywords: перехідні процеси; розгін гідроприводу; система роторів; розподільна система; тиск; крутний момент; витрата робочої рідини; кутова швидкість; динамічні характристики; transient processes; hydraulic drive acceleration; rotor system; distribution system; pressure; torque; working fluid flow rate; angular velocity; dynamic characteristics